PERANCANGAN APLIKASI SISTEM INFORMASI SELEKSI PESERTA DIDIK BARU BERBASIS WEBSITE DENGAN METODE SPIRAL - Sri Rama Putri; Muhamad Rafi’ul Fajar (Journal of Research and Publication Innovation, 2025)
The need for speed, accuracy, and accuracy of distribution information, is the main demand of educational institutions that require a fast and precise information management system because it can support and facilitate in achieving targets and goals, especially in accepting new students. Bantar Panjang Elementary School still uses manual methods to introduce or provide information on new student registration. Therefore, an online new student admission system is needed that can help schools to manage registration data. In addition, this system is also expected to help the selection of prospective new students so that the selection process will be easier and does not take a long time. In addition, the online system will also help prospective new students to find out the registration results easily and do not need to come directly to school. Therefore, the website is one of the most widely accessed information media and helps the dissemination of information digitally. With this website, it is hoped that the wider community can get to know Bantarpanjang Elementary School. Prospective students do not need to bother visiting Bantarpanjang State Elementary School just to see announcements or information related to new student registration directly, whenever and wherever they are, they can do it via a computer connected to the internet, so that the entire community will feel safe not having to leave the house to get information. The information presented will greatly assist users in obtaining information about Bantarpanjang State Elementary School.